ASPECTS OF CONSTRUCTION OF THE POWER SUPPLY SYSTEM OF AVIATION ENTERPRISES USING SOURCES OF DISTRIBUTED GENERATION - BOYKO, SERHIY; VYSHNEVSʹKYY, SVIATOSLAV; POLISHCHUK, PETRO; SOBCHUK, NATALIYA; REUTA, ALLA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The aviation industry is a component of the transport structure of any developed country. In Ukraine, among other types of transport, air transport occupied a worthy place before the armed confrontation. Undoubtedly, the time will come and the further restoration of air transport in Ukraine is inevitable. Unmanned aerial vehicles, which have become indispensable components of reconnaissance operations, are also actively developing today. The main factor in ensuring the functioning of aviation enterprises is electricity supply. Undoubtedly, the power supply systems of aviation enterprises are made with double redundancy, however, as world and domestic experience shows, there is still a need to increase the level of reliability of the power supply systems of aviation enterprises. Therefore, the task of introducing additional generating capacities into the power supply systems of aviation enterprises remains relevant. The advantages of implementing the proposed power supply scheme for aviation enterprises using distributed sources of electrical energy are: the block structure of the system, which consists of typical electrotechnological devices, which makes it possible to relatively quickly provide electricity to responsible consumers of electrical energy, and makes it possible to increase generation capacity in the future. Meanwhile, today’s promising ones are electric energy accumulators based on hydrogen technologies, among which fuel cells should be singled out. Not the last role is played by the safety of operating fuel cells in the conditions of aviation enterprises, which maintains aviation safety at a sufficient level. The article highlights the vision proposed by the authors regarding the reconfiguration of the existing power supply systems of aviation enterprises using sources of distributed generation. This approach should increase the safety of operation by accumulating systems on the reliability of power supply systems of aviation enterprises. The proposed power supply system using sources of distributed generation for operation in the conditions of aviation enterprises makes it possible for the power supply system of these enterprises to acquire new properties due to the modularity of generating units of sources of distributed generation of electric energy.